Raw data of physical oceanography during RV MARIA S. MERIAN cruise MSM131 - Thomas Pape; Miriam Römer; Eberhard Kopiske; Gerhard Bohrmann (PANGAEA, 2025)
During cruise MSM131 conductivity-temperature-depth profiles were measured during 23 hydrocasts with the CTD/Rosette (CTD-RO) system of RV MARIA S. MERIAN above the Jøtul hydrothermal field and the northern Molløy Ridge area. The CTD system consisted of a CTD 911plus deck unit with two conductivity sensors (SBE 4C), two temperature sensors (SBE 3plus), a single pressure sensor (SBE 9plus), and two SBE 5T pumps (all components from Sea-Bird Scientific). The system was also equipped with a dissolved oxygen sensor (SBE 43), a fluorometer/turbidity sensor (WET Labs ECO FLNTURTD), and a Teledyne Benthos PSA-916 altimeter. In addition, an oxidation-reduction potential (ORP) sensor from NOAA/PMEL, USA, was mounted in the rosette. All oceanographic data was recorded and processed with the Seasave (V7.22) and SBE Data Processing (V7.22.0) software programs. Acoustic underwater positioning was achieved with the ships extquotesingle own Sonardyne Ranger 2 Gyro USBL HPT 7000 with the transponder being attached to the frame of the rosette.